Introduction to Windows Azure - Li, Henry (Apress, 2012)
The cloud platform is getting more and more attractive to the computing world. Today, service-oriented architecture (SOA) and aspect-oriented programming (AOP) techniques are widely used in enterprise solutions. A question an IT management team or a software development team may ask is, what is the next trend going to be? Cloud computing seems to be the right answer. Different names are used for this kind of platform, including utility computing, on-demand platform, and platform as a service. A set of new buzzwords has been widely used in relation to cloud computing, such as Program as a Service (PaaS), Software as a Service (SaaS), and anything you can think of as a service (XaaS). For any enterprise business solution, the cost to build, deploy, host, and maintain infrastructures and applications is always challenging for the administrative and development teams in an organization. The cloud platform aims to take away the cost of building, deploying, updating, and maintaining. Applications used in organizations today are called on-premises applications. In this case, infrastructure and storage facilities, as well as the applications, are hosted within an organization. By contrast, both storage and application services provided by the cloud platform are hosted externally (they can also be hosted within an organization for a local cloud environment) through the Internet. Microsoft offers such services to host both storage and applications from its data centers via its Windows Azure cloud platform.